Proses Perancangan Peraturan Perundang-Undangan di Indonesia Tantangan dan Reformasi dalam Era Digital - Endah Ratnawati; Witandri Witandri; Ahmad Zaki Rayhan; Masharin Masharin; Arif Hardiyanto; Agus Prasetyo; Firman Adi Candra (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This article examines the process of legislative drafting in Indonesia, emphasizing the stages of law formation, the roles of the House of Representatives (DPR) and the government, and the challenges arising in the digital era. The primary focus is on the revision of Law No. 11 of 2008 on Electronic Information and Transactions (UU ITE), which reflects efforts to adapt legal frameworks to technological advancements. Through normative juridical analysis, the article identifies issues such as regulatory disharmony, overload of legal products, and the need for AI-based reforms. The findings indicate that reforms like digitalization of legislative processes and the application of regulatory guillotine can enhance efficiency and legal certainty. Recommendations include integrating technology for more inclusive public participation.